6 - Covid-19 Pandemic Exposes the Resilience Vulnerability of Ghana’s EQA System for Higher Education - Ansah, Francis; Swanzy, Patrick; Mpondi, Douglas; Asamoah, Gloria; Nyondo, Joy (CODESRIA Bulletin, 2023)